Integrated endocrinology - Laycock, John F.; Meeran, Karim (Chichester, West Sussex : Wiley-Blackwell, 2012)
This innovative textbook provides a readable, contemporary and fully integrated introduction to endocrine glands, their hormones and how their function relates to homeostasis. It explores the pathology of endocrine disease by relating the underpinning science through a wealth of clinical scenarios and examples. The book integrates basic and clinical aspects for a range of endocrine glands and their hormones and includes a number of specialist chapters that also address areas of intense research and clinical interest including the regulation of salt, appetite and endocrine-immune interactions.
The molecular basis of hormones -- The hypothalamus and the concept of neurosecretion -- The pituitary gland (1) : the anterior lobe (adenohypophysis) -- The pituitary gland (2) : the posterior lobe (neurohypophysis) -- Diseases of the pituitary gland -- The gonads (1) : testes -- The gonads (2): ovaries -- The endocrine control of puberty -- The hormones of pregnancy, parturition and lactation -- The adrenal glands (1) : adrenal cortex -- The adrenal glands (2) : adrenal medulla -- The endocrine control of salt and water balance -- The thyroid gland and its iodothyronine hormones -- The islets of Langerhans and their hormones -- Diabetes mellitus -- The gut/brain axis -- Hormones, endocrine tumours, and the gut -- The parathyroids, the endocrine kidney, and calcium regulation -- The genetics of endocrine tumours -- Future prospects.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Endocrine Glands; Endocrine System Diseases; Hormones; Endocrinology; MEDICAL -- Endocrinology & Metabolism; Endocrinology; Electronic books; Electronic books